(untitled) (Research, Society and Development, 2020)
This article makes a brief study of the place occupied by Coelho Neto within the historiography of Brazilian literature, considering the succession of positive and negative receptions that the he had throughout his career as a writer and, through critical-theoretical studies, aims at clarifying how literary and extraliterary factors influenced the reading audience and the interpretations made regarding the writer’s works. It was possible to conclude that, in different spheres, the interpretations made on Coelho Neto’s works were conditioned by ideals to be reached and by the interest of discrediting the writer from Maranhão.